Case Report: Iatrogenic dyspnea and respiratory failure in a multiple myeloma patient treated with carfilzomib - Bertuglia, Giuseppe; Verardo, Mattia; Scaldaferri, Matilde; Mangiapia, Mauro; Bruno, Benedetto; Larocca, Alessandra (Frontiers in Oncology, 2025)
Carfilzomib, a second-generation proteasome inhibitor, is approved for the treatment of relapsed or refractory multiple myeloma, with cardiovascular toxicity being the most common concern. Nevertheless, pulmonary complications have been reported and may complicate differential diagnosis. We describe the case of a 79-year-old man with multiple myeloma who developed two episodes of acute respiratory failure temporally related to carfilzomib administration. After six cycles of therapy, the patient presented with dyspnea, hypoxemia, and bronchospasm requiring hospitalization. Extensive investigations excluded infection, pulmonary embolism, and cardiac dysfunction, and symptoms resolved with supportive therapy. Carfilzomib was resumed at reduced dose, but a second episode of respiratory failure occurred shortly after re-exposure, leading to definitive discontinuation. Pulmonary function testing demonstrated recovery to baseline values after drug withdrawal. This case underlines the need for awareness of non-cardiogenic respiratory adverse events in patients treated with carfilzomib, especially those with pre-existing pulmonary conditions. Careful monitoring and appropriate diagnostic work-up are essential, and drug re-challenge should be avoided in case of severe respiratory events. Recognition of these complications may improve patient safety and guide therapeutic decisions in multiple myeloma.